Accounting Workshop for Students at Kristoforus 2 High School Using the Accurate App - Nastasya Cindy Hidajat (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: Accounting education at the high school level is still dominated by a theoretical approach, resulting in relatively low levels of practical understanding and student interest in accounting. This Community Service (PKM) activity aims to improve students’ understanding, digital literacy, and interest in accounting by using the Accurate application as a technology-based learning tool. Method: The event was held at Kristoforus 2 High School on April 17, 2026, and involved 21 11th-grade students. The method used was a workshop with an educational-participatory approach, featuring an introduction to accounting, a demonstration of the Accurate application, guided practice, discussions, and an evaluation using a questionnaire. Results and Discussion: Before the intervention, most students had never used accounting software and only had a theoretical understanding of accounting concepts. The evaluation results showed that all participants found the activity beneficial, with 19 students giving a score of 5 and 10 students giving a score of 4 for the increase in knowledge gained. Implications: This program helps improve students' accounting and digital literacy and supports more interactive and context-based accounting education.